2015
DOI: 10.5498/wjp.v5.i3.315
|View full text |Cite
|
Sign up to set email alerts
|

Motor abilities of children and adolescents with a psychiatric condition: A systematic literature review

Abstract: Research suggests that motor impairment is highly prevalent in some psychiatric conditions, particularly ASD and ADHD. However, future work is necessary to draw sound conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 71 publications
2
37
0
1
Order By: Relevance
“…In particular, unlike infants with normal fidgety movements at 3-4 months, children with mildly abnormal GMs were significantly more distractible, inattentive and hyperactive as assessed by the Groningen Perinatal Project Questionnaire (GPPQ) and the DSM-IV ADHD Questionnaire for Attention-Deficit/Hyperactivity Disorder. Another study [40] indicated that abnormal GMs at both writhing and fidgety age were significantly associated with the presence of ADHD only when it was co-occurrent with another psychiatric diagnosis, but not when it was present in isolation. Furthermore, abnormal GMs at fidgety age were related to a higher total score on the DSM-IV ADHD questionnaire, and in particular, to higher subscores for hyperactivity and impulsivity, and lower subscores for inattention.…”
Section: Spontaneous Movements During the First 3 Months Of Agementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, unlike infants with normal fidgety movements at 3-4 months, children with mildly abnormal GMs were significantly more distractible, inattentive and hyperactive as assessed by the Groningen Perinatal Project Questionnaire (GPPQ) and the DSM-IV ADHD Questionnaire for Attention-Deficit/Hyperactivity Disorder. Another study [40] indicated that abnormal GMs at both writhing and fidgety age were significantly associated with the presence of ADHD only when it was co-occurrent with another psychiatric diagnosis, but not when it was present in isolation. Furthermore, abnormal GMs at fidgety age were related to a higher total score on the DSM-IV ADHD questionnaire, and in particular, to higher subscores for hyperactivity and impulsivity, and lower subscores for inattention.…”
Section: Spontaneous Movements During the First 3 Months Of Agementioning
confidence: 99%
“…This may be partly due to the relative immaturity of cognitive functions related to sustained attention and focused activity during the first months of life, and to the consequent difficulty in reliably assessing them. Increasing evidence suggests that specific motor behaviors observed during the first months of life may be a marker of neurodevelopmental disorders, which show clinical and genetic overlap with ADHD [40]. Some authors suggest that increased activity in infancy could be considered an early sign of ADHD [38,[41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Na comparação do equilíbrio postural de crianças com deficiência intelectual e em desenvolvimento típico (grupo controle) foi possível verificar, por meio de parâmetros quando comparado às crianças com desenvolvimento típico em vários aspectos, incluindo equilíbrio estático e dinâmico 19 . Em uma revisão sistemática, realizada por Van Damme e colaboradores 20 , a diminuição das habilidades motoras é frequentemente relatada em deficientes intelectuais. A revisão mostra que em 24 estudos, os indivíduos com déficit de atenção associado com a hiperatividade obtiveram uma menor performance com relação aos pares de desenvolvimento típico.…”
Section: Conclusãounclassified
“…There is growing evidence that individuals with DCD have elevated levels of internalising symptoms compared to their typically developing (TD) peers (Mancini, Rigoli, Cairney, Roberts, & Piek, ; Mancini, Rigoli, Roberts, & Piek, ). Research has also found associations between motor ability and internalising symptoms in community samples of TD children and adults (Poole et al., ; Rigoli, Piek, & Kane, ; Wilson, Piek, & Kane, ), an increased risk of psychiatric disorders in individuals with DCD (Rasmussen & Gillberg, ), and impaired motor ability in individuals with common psychiatric disorders (Damme, Simons, Sabbe, & van West, ).…”
Section: Introductionmentioning
confidence: 99%